Strategy Under Uncertainty: Open Innovation and Strategic Learning for the Iceland Ocean Cluster - Mattos-Hall, Joseph Anthony, 1988- (2014)
Uncertainty is the principle challenge of the future. Strategy attempts to relate organisations to their respective environments and thereby deal with uncertainty better. The present analysis accepts and recognises uncertainty as an intractable facet of the order under which our affairs are conducted, and shows that a considerable amount of work in the field of strategy fails to do this. The analysis begins by outlining the tenets of some of these contributions to strategy that fall under the “planning” and “positioning” schools, demonstrating that they are methodologically biased. The analysis then turns to critique these schools from the “learning” school approach. In doing this, the analysis argues that strategy is an emergent process that is considerably vulnerable to environment-related volatility. This hopes to create a “realised” strategy; a confluence of “intended” and “emergent”. The analysis seeks instead to domesticate uncertainty, to harness it for the better, arguing that knowledge is best harnessed when it comes from diffuse, disaggregated inputs, leading to large spillover effects. By feeding these inputs into not only into the innovation but also the market process, this analysis puts forward a new a kind of emergent strategy based learning, Open Innovation (OI) and “convex” principles that benefit from volatility, arguing for crowdsourcing and crowdfunding. This is then applied to the case study of the Iceland Ocean Cluster (IOC), and the analysis argues that the benefits of clustering can be combined with O principles to bring together the benefits of co-location and disaggregation for a positive innovative effect. To this end, the present analysis has tied together a range of disciplines from uncertainty theory, history, economics, economic geography; the philosophy of science; naturalistic cognitive psychology; social network theory; the history of technology; competition and policy interwoven with practical examples.